Effects of the Medium-Wall Modulus Contrast on the Pulse Wave Imaging (PWI) of Aortic Phantoms - Shahmirzadi, Danial; Lin, Kexin; Li, Han (British Journal of Healthcare and Medical Research, 2016)
Given its close correlation to cardiovascular pathologies, change in arterial stiffness has been deemed as a reliable biomarker for predicting cardiovascular events. The feasibility of using the ultrasound-based method of Pulse Wave Imaging (PWI) for estimating the arterial Pulse Wave Velocity (PWV) as surrogate of the wall stiffness has shown capacity for enhancing cardiovascular noninvasive diagnosis. The Moens-Korteweg equation, which is the baseline for the modulus-PWV relationship, does not account for factors such as the stiffness of the surroundings and the continuous pulsatile flow; while these factors are prevalent in phantom and in vitro PWI studies and could affects the PWV measurements. The objective of the present study is to quantify the correlation between the wave propagations and the stiffness of the surrounding medium, under various flow speeds. The PWV results were quantified in terms of their r2 and SNR, indicating the uniformity of the waves and variations in the measurements. The characteristic curves were developed in terms of the wall-to-medium modulus contrast that could be used as the reference for selecting the optimized gel and medium stiffness parameters that minimize the boundary conditions effects and maximize the SNR and r2.